Legal Implications of the Deed of Land Sale and Purchase Agreement that is Still in the Process of Being Finalized for Legal Certainty for the Parties - Julianty, Julianty; Fajar Riyanto, Taufan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze: 1)Legal implications of the use of a Deed of Sale and Purchase in land sale and purchase transactions that are still in the process of being divided. 2). Legal certainty for buyers in land sale and purchase transactions with a Deed of Sale and Purchase when the land certificate is still in the process of being divided. This type of research is normative legal research. The approach method in this research is a case study approach and a statute approach. The type of data in this research is secondary data. The data collection method uses library techniques (study documents). The analysis in this research is prescriptive. The results of the study concluded: 1) The legal implications of the use of a Deed of Sale and Purchase in land sale and purchase transactions that are still in the process of being divided are that the use of PPJB has significant legal consequences because it is only obligatory and has not transferred ownership rights as regulated in Article 37 of PP Number 24 of 1997. This condition causes buyers to not obtain legal protection for property, cannot change the name, and is at high risk if the seller abuses land rights. Based on Soeroso's Theory of Legal Consequences, a PPJB for undivided land has three legal consequences: the emergence of a new legal situation in the form of a conditional sale and purchase agreement, the formation of a reciprocal legal relationship between the seller and the buyer, and the emergence of legal sanctions in the event of default. 2) Legal certainty for buyers in land sale and purchase transactions with a Deed of Sale and Purchase Agreement when the land certificate is still in the process of being divided is not fully guaranteed. Although the UUPA, PP Number 24 of 1997, and Permen ATR/BPN Number 16 of 2021 have provided the legal basis for land registration, the PPJB only creates an obligatory relationship without transferring ownership rights. As a result, buyers do not have legal certainty regarding the property and only have the right to demand the implementation of the sale and purchase after the division is complete. Registration of the PPJB at the Land Office only provides administrative certainty, not legal ownership. Differences in judges' interpretations of the legal force of the PPJB, as seen in the Decisions of the Yogyakarta District Court No. 63/Pdt.G/2020/PN.Yyk and the Yogyakarta High Court No. 13/PDT/2021/PT.Yyk demonstrates a lack of substantive legal certainty. Therefore, regulatory updates are needed to clarify the legal standing of PPJBs to strengthen protection for buyers in good faith and ensure the process of deed separation and AJB is carried out with certainty and uniformity.